Comparative Analysis of Pain Relief and Adverse Effects of Ibuprofen versus Naproxen in Elderly Knee Osteoarthritis: Pain Relief and Ibuprofen versus Naproxen in Elderly Knee Osteoarthritis - Marfani, Suhail; Khan, Ayesha; Zubair, Muhammad Ali; Naeem, Nadia; Anwar, Khawar; Ishrat, Shabzain (Pakistan Journal of Health Sciences, 2025)
Osteoarthritis (OA) has no definitive cure, and to improve the quality of life, analgesic medications are used. Objectives: To evaluate ibuprofen and naproxen in elderly patients with knee osteoarthritis in terms of pain relief (primary outcome) and adverse effects (secondary outcome). Methods: This comparative analytical study was conducted at the Rheumatology Clinic of Shahida Islam Medical College and Hospital from June to November 2024. Following ethical approval, patients aged over 50 years with stage I–III knee OA willing to participate were included. Exclusion criteria were stage IV OA, systemic or rheumatologic co-morbidities (e.g., hypertension, diabetes), prior use of naproxen or ibuprofen within one month, and history of surgery within the past year. Results: A total of 310 participants were enrolled, equally divided between two groups: Naproxen Sodium (440/660 mg, n=155) and Ibuprofen (1200 mg, n=155). Both drugs significantly reduced pain from baseline to day 7 post-medication, including pain at rest, on weight-bearing, during passive movements, morning stiffness, and pain throughout the day and night (p<0.01, assessed via Visual Analogue Scale). Conclusions: Minimal side effects were observed in both groups. Naproxen and ibuprofen were both effective and well-tolerated options for pain relief in elderly patients with knee OA.